A Rare Case of Coexistence of Borderline Lepromatous Leprosy with Tuberculosis Verrucosa Cutis - Biswajit Dey; Debasis Gochhait; Nagendran Prabhakaran; Laxmisha Chandrashekar; Biswanath Behera (Case Reports in Infectious Diseases, 2016)
Occurrence of pulmonary tuberculosis with leprosy is known but association of cutaneous tuberculosis with leprosy is rare. We report a case of borderline lepromatous leprosy coexistent with tuberculosis verrucosa cutis in a 29-year-old male, who presented with multiple skin coloured nodules and hyperkeratotic scaly lesions of 3-month duration. Dual infections are associated with high mortality and morbidity. Therefore early diagnosis and management helps to reduce mortality and to mitigate the effects of morbidity.